the The Impact of Educational Leadership on Teachers’ AI Integration and Digital Transformation: A Meta-Analysis: Dampak Kepemimpinan Pendidikan terhadap Integrasi AI dan Transformasi Digital Guru: Sebuah Meta-Analisis - Sogalrey, Febi Adriana mutiara; Sobri, Ahmad Yusuf (Jurnal Riset Manajemen Indonesia, 2025)
The rapid advancement of artificial intelligence (AI) has accelerated digital transformation in education, compelling teachers to integrate technology into their teaching practices. This study aims to analyze the impact of educational leadership on teachers’ AI integration through a Systematic Literature Review (SLR) combined with meta-analysis. Data were retrieved from the Scopus database using the keywords “Educational Leadership”, “Teachers’ AI Integration”, and “Digital Transformation”. The selection process followed the PRISMA protocol and yielded six studies that met the inclusion criteria. Analysis was conducted using a random-effects model with RStudio software. The meta-analysis revealed that educational leadership has a positive and significant effect on teachers’ AI integration, with a pooled effect size of r = 0.44 (95% CI [0.37–0.51]), which falls into the medium category. The heterogeneity test resulted in I² = 71.8% (p = 0.0033), indicating substantial variability across studies, likely influenced by institutional contexts, respondent characteristics, and leadership models examined. The funnel plot analysis indicated a moderate publication bias, although the overall relationship remained consistently positive. The findings underscore that transformational and digital leadership are key factors in fostering teachers’ readiness to adopt AI and in accelerating digital transformation in education. This study contributes to the leadership literature by positioning AI integration as a new indicator of leadership effectiveness in the 21st century, while also providing practical implications for policymakers and educational leaders in designing technology-driven school transformation strategies.